2008
DOI: 10.1159/000149569
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Comparison of Once Daily Insulin Detemir and Glargine in Reducing Weight Gain and Hypoglycaemic Episodes when Administered in Addition to Conventional Oral Anti-Diabetic Therapy in Patients with Type-2 Diabetes

Abstract: Aims: Basal insulin administered to type-2 diabetic patients with poor glycaemic control when managed with oral anti-diabetics (OADs) alone can lead to an increased risk of weight gain and hypoglycaemia. In the absence of head-to-head trials, an indirect comparison of the once-daily insulin detemir with insulin glargine was conducted on the following outcomes: weight gain, hypoglycaemic episodes, and HbA1c. Methods: Parallel-group randomised controlled trials of at least 20 weeks duration that compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…The weight benefit pattern seen in this analysis among patients with higher BMIs has been observed in similar studies with insulin detemir 20,31 . Likewise, previous trials in patients with T2DM have documented less weight gain with insulin detemir versus NPH insulin [14][15][16] and insulin glargine 32,33 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The weight benefit pattern seen in this analysis among patients with higher BMIs has been observed in similar studies with insulin detemir 20,31 . Likewise, previous trials in patients with T2DM have documented less weight gain with insulin detemir versus NPH insulin [14][15][16] and insulin glargine 32,33 .…”
Section: Discussionmentioning
confidence: 84%
“…Mean changes in fasting blood glucose and fasting blood glucose variability were -3.62 mmol/L (SD AE 2.93; p50.0001) and À0.48 mmol/L (SD AE 1.03; p50.0001), respectively. Body weight decreased by a mean 0.5 kg (SD AE 3.3; p50.0001), with weight loss or no weight change occurring in a substantial percentage of patients in each BMI category ( 525, [25][26][27][28][29][30][30][31][32][33][34][35], and 435 kg/m 2 ). Patients with higher baseline BMI lost the most weight, with the greatest weight loss (-1.20 kg) reported in those with BMI 435 kg/m 2 .…”
mentioning
confidence: 99%
“…A previous meta-analysis 15 has reported significantly less weight gain with detemir than glargine, where the analysis was restricted to only one study of detemir and four glargine trials, all of which are included in the present analysis. 15 Our analysis demonstrates that individuals treated with detemir require a higher dose of insulin compared with individuals treated with glargine in order to achieve the same improvement in glycemic control. In the study by Rosenstock et al, 2 55% of the individuals required twice-daily dosing with detemir by the end of the 52-week treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Once-daily dosing with glargine and once-or twice-daily dosing with detemir are associated with further improvement in glycemic control and a lower risk of hypoglycemia versus NPH insulin. 13,14 Some studies in type 1 diabetes mellitus and T2DM have suggested that treatment with detemir results in less weight gain compared with either glargine 2,15 or NPH.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 99%
“…Meta-analysis of five parallel group randomized controlled trials of at least 20 weeks' duration that compared once daily evening insulin glargine or insulin detemir with a common comparator, NPH insulin (evening administration), showed that patients with T2DM (n = 2092) who received evening insulin detemir gained significantly less weight (−1.22 kg) than those treated with insulin glargine (−0.29 kg, P = 0.010). 51 Importantly, this analysis focused on insulin naïve, T2DM patients poorly controlled with oral antidiabetes drugs, which are the patients most likely to be switched to insulin therapy in clinical practice. The beneficial effects of insulin detemir on weight change appear greatest in patients with high body weight or BMI at the initiation of treatment.…”
Section: Insulin Detemirmentioning
confidence: 99%